Tuberculin Skin Testing versus Interferon-Gamma Release Assay among Users of a Public Health Unit in Northeast Portugal - Andrea Luísa Fernandes Afonso; Bruno Miguel Morais Pires; Cristina Martins Teixeira; António José Nogueira (Karger Publishers, 2021)
The screening of groups with a high risk for developing tuberculosis (TB) is a priority in order to control this disease. Since there is no gold standard for the diagnosis of latent TB infection (LTBI), both the tuberculin skin test (TST) and the interferon-gamma release assays (IGRA) have been used for this purpose. The aim of this study was to determine the proportion of LTBI by using the TST and the IGRA tests, and to assess the risk factors related with discordant results between tests across several risk groups advised for screening in Northeast Portugal. Data were collected from the database of patients with suspected LTBI and advised for the screening in a public health unit (January 2014 to December 2015). The proportion of LTBI was computed using both tests. Logistic regression models assessed risk factors for a positive test and for discordant results between tests. The adjusted odds ratio (OR) and respective 95% confidence interval (95% CI) were obtained. Out of 367 patients included in the analysis, 79.8% had a positive TST and 46.0% of them had a positive IGRA. In comparison with contacts of active TB cases, healthcare workers and inmates presented higher odds of TST positivity (OR 4.38, 95% CI 1.59-12.09 and OR 4.74, 95% CI 1.45-15.49, respectively), but immunocompromised people presented lower odds of TST positivity (OR 0.14; 95% CI 0.06-0.31). Instead, healthcare workers (OR 0.44, 95% CI 0.24-0.80) and immunocompromised people (OR 0.24, 95% CI 0.10-0.56) presented lower odds of a positive IGRA. There were 42.0% concordant positive results, 16.1% concordant negative results, and 41.9% discordant results, with healthcare workers presenting higher odds of discordant results (OR 3.34, 95% CI 1.84-6.05). The proportion of LTBI estimated by TST and IGRA among people advised for screening in our setting is high, highlighting the need of preventive strategies. Among healthcare workers, TST results should be read with caution as the higher proportion of discordant results with a positive TST suggests the impact of the booster reaction in this group.